2013
DOI: 10.1007/s00405-013-2755-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficiency of quadrivalent HPV (types 6/11/16/18) vaccine in patients with recurrent respiratory papillomatosis

Abstract: The aim of the study was to assess the clinical efficiency of quadrivalent HPV (types 6/11/16/18) vaccine in patients with recurrent respiratory papillomatosis (RRP). This was a prospective study of patients with RRP treated from January 2009 to July 2012 at the Ear, Nose and Throat Department of the Emergency County Hospital of Cluj-Napoca, Romania. Demographic characteristics, onset of RRP, HPV typing, use and number of cidofovir injections, number of surgeries for RRP per year, and use of human papillomavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
2
30
0
1
Order By: Relevance
“…However, the vaccine trials indicate that vaccination does not treat existing infection or disease. Despite case reports and retrospective reviews temporally associating vaccination with disease remission, there is currently no randomized trial evidence that vaccination is useful therapeutically in RRP patients . Rather, RRP may now be prevented via vaccination of females, therefore dramatically reducing the chance of infant exposure to HPV6/11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the vaccine trials indicate that vaccination does not treat existing infection or disease. Despite case reports and retrospective reviews temporally associating vaccination with disease remission, there is currently no randomized trial evidence that vaccination is useful therapeutically in RRP patients . Rather, RRP may now be prevented via vaccination of females, therefore dramatically reducing the chance of infant exposure to HPV6/11.…”
Section: Introductionmentioning
confidence: 99%
“…Despite case reports and retrospective reviews temporally associating vaccination with disease remission, there is currently no randomized trial evidence that vaccination is useful therapeutically in RRP patients. [14][15][16][17] Rather, RRP may now be prevented via vaccination of females, therefore dramatically reducing the chance of infant exposure to HPV6/11. In Australia, a quadrivalent vaccine program (for females aged 12-26 years) commenced in 2007 and achieved high coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Un estudio prospectivo no aleatorizado realizado en Rumania por Chirla y col 16 en 2014, de 31 pacientes con PRR en su presentación juvenil (diagnosticado en menores de 17 años) y adulta (diagnosticado en mayores de 17 años), utilizó Gardasil ® según esquema estándar de 3 dosis en 13 pacientes con papilomatosis severa (más de tres cirugías al año) que recurrió luego de tratamiento con resección quirúrgica y cidofovir, y se mantuvieron en seguimiento por 1 año. El estudio concluyó que el 85% (IC 95% [54,44-99,41]) de los pacientes intervenidos con la vacuna tetravalente no presentó evidencia de recurrencia a un 1 año de la intervención.…”
Section: Resultsunclassified
“…Several case reports and case series regarding the clinical effect of HPV vaccination for RRP and RRP have been published. One of these publications described only a single‐year effect of the quadrivalent HPV vaccination, demonstrating the suppression of tumor recurrence in approximately 80% of patients with RRP . Another article reported that recurrence was not observed in nearly half of the study subjects at 1 year after Gardasil (Merck & Co.) vaccination .…”
Section: Discussionmentioning
confidence: 99%